MICROPLASTICdays - Kalčíková, Gabriela (knjige, 2024)
This book compiles the abstracts of invited presentations given during MICROPLASTICdays, conducted from 16.–18. April 2024 at the Faculty of Chemistry and Chemical Technology, University of Ljubljana (UL FKKT), Slovenia.